The Strong Correlation Between Pain Interference and Abnormal Nutritional Status in Older Adults With Chronic Musculoskeletal Pain - Narucha Komolsuradej; Siwaluk Srikrajang; Norrapat Rangsiprakarn; Arya Wongaree; Chonnapat Wasusathapon; Darat Kanjanakomut; Vannarat Nukaew; Wannasak Cheutalay; Suppawit Kaewpipat; Sirinkit Hoonthong; Sochealing Ung; Khanin Iamthanaporn (SAGE Publishing, 2023)
Objectives: Musculoskeletal pain, one of the most common issues faced by older adults, has multidimensional effects including an increased risk of malnutrition. Therefore, this study aimed to investigate the association between pain interference and nutritional status in older adults with chronic musculoskeletal pain. Methods: In this cross-sectional study, data were collected from older adults (age: >60 years) using the brief pain inventory and mini nutritional assessment questionnaire. The correlation between pain interference, pain severity, and nutritional status was assessed using the chi-square test and Spearman's rank correlation. Multiple logistic regression analysis was used to analyze the variables associated with abnormal nutrition status. Results: Overall 241 older adults were recruited in the study. The median (IQR) age of the participants was 70 (11) years, pain severity subscale was 4.2 (1.8), and pain interference subscale was 3.3 (3.1). Abnormal nutritional status was positively correlated with pain interference (Odds ratio [OR]: 1.26; 95% confidence interval [CI]: 1.08-1.48; P  = .004), pain severity (OR: 1.25; 95% CI: 1.02-1.53; P  = .034), age (OR 1.06; 95% CI: 1.01-1.11, P  = .011), and hypertension (OR = 2.17; 95% CI: 1.11-4.26; P  = .024). Conclusions: This study reports a strong correlation between pain interference and nutritional status. Therefore, pain interference can be a useful pain assessment tool to indicate risk of abnormal nutritional status in older adults. In addition, related factors, including age, underweight, and hypertension, were associated with a higher risk of malnutrition.